Thirty-three new species of Agromyzidae (Diptera) from the United States and Canada, with new host and distribution records for 154 additional species - Eiseman, Charles S.; Lonsdale, Owen; Feldman, Tracy S.; Linden, John Van Der (Zootaxa, 2026)
We present novel rearing records of Agromyzidae (Diptera) from throughout the United States and eastern Canada. We provide new rearing records for 154 species, plus 15 others whose identification is tentative or only to genus due to the absence of male specimens. For each species, we describe the leaf mines or other larval habits and review existing host, distribution, and phenological data. We provide the first rearing records for 19 species (Agromyza echinalis Lonsdale, A. kincaidi Malloch, A. pallidiseta Malloch, A. tacita Spencer, A. valdorensis Spencer, A. virginiensis Spencer, Liriomyza conclavis Lonsdale, L. hilairensis Lonsdale, L. montana Sehgal, L. nordica Spencer, M. eoflacensis Lonsdale, M. scrophulariae Spencer, M. subvirens (Malloch), Ophiomyia vockerothi Spencer, Phytoliriomyza conjunctimontis (Frick), P. consulta Spencer, P. imperfecta (Malloch), P. pacifica (Melander), and Phytomyza (Napomyza) nugax (Spencer)); the first full account of the larval biology of Amauromyza karli (Hendel); and the first unambiguous host record for Phytomyza sehgali Spencer, along with (for the remaining 133 confidently identified, previously known species) 166 other new host species records, 70 new host genera, and seven new host families. We report 200 new state and provincial records, including the first confirmed North American records for Agromyza alnibetulae Hendel, Aulagromyza populi (Kaltenbach), Calycomyza steviae Spencer, Liriomyza avicenniae Martinez, L. mikaniovora Spencer, and Phytomyza spinaciae Hendel; the first confirmed USA records for Agromyza valdorensis Spencer, Calycomyza sonchi Spencer, Cerodontha (Dizygomyza) scirpivora Spencer, Phytomyza mitellae Griffiths, and P. pedicularicaulis Spencer; and the first confirmed Canadian records for Calycomyza cynoglossi (Frick), Liriomyza eupatoriella Spencer, L. valerianivora Eiseman & Lonsdale, and Ophiomyia kwansonis Sasakawa. The above counts refer to records confirmed by examination of reared specimens; numerous additional new host and distribution records are reported based on photographed mines and tentatively identified females. We clarify the identity and hosts of Calycomyza novascotiensis Spencer and synonymize C. michiganensis Steyskal syn. nov. with it; we also consider Liriomyza carphephori Eiseman, Lonsdale & Feldman syn. nov. to be a synonym of L. cracentis Lonsdale, and Ophiomyia parda Eiseman & Lonsdale syn. nov. to be a synonym of O. quinta Spencer. A narrowed concept of Agromyza parca Spencer is provided. We describe and provide natural history information for the following 33 new species: Agromyza celtitexana Eiseman & Lonsdale, A dichanthelii Eiseman & Lonsdale, A. parasoka Eiseman & Lonsdale, A. torta Eiseman & Lonsdale, Calycomyza altissimi Eiseman & Lonsdale, C. baccharidis Eiseman & Lonsdale, C. brickelliae Eiseman & Lonsdale, C. diazi Eiseman & Lonsdale, C. salviae Eiseman & Lonsdale, C. serotini Eiseman & Lonsdale, Haplopeodes vittatus Eiseman & Lonsdale, Liriomyza arenicollis Eiseman & Lonsdale, L. calasclepiadis Eiseman & Lonsdale, L. konza Eiseman & Lonsdale, L. lobeliae Eiseman & Lonsdale, L. mikaniella Eiseman & Lonsdale, L. nyx Eiseman & Lonsdale, L. rivinae Eiseman & Lonsdale, Melanagromyza arcana Eiseman & Lonsdale, M. ayla Eiseman & Lonsdale, M. blephiliae Eiseman & Lonsdale, M. mikannula Eiseman & Lonsdale, M. phloxicaulis Eiseman & Lonsdale, Ophiomyia astericosta Eiseman & Lonsdale, O. cophina Eiseman & Lonsdale, O. erigeronis Eiseman & Lonsdale, O. lactucae Eiseman & Lonsdale, O. sequentia Eiseman & Lonsdale, O. verni Eiseman & Lonsdale, Phytomyza antennariae Eiseman & Lonsdale, P. cicutiphaga Eiseman & Lonsdale, P. dasycarpi Eiseman & Lonsdale, and P. dioici Eiseman & Lonsdale. In addition, we provide keys to the adults and immature stages of Agromyza species feeding on Celtis L. (Cannabaceae), including those whose identities require further investigation.